Efisiensi Model Mesh Kasus Deteksi Simulasi Korosi Beton Bertulang Menggunakan Metode Axisymmetric Mesh Problem - Muhammad Ihsan; Herdi Susanto (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
In this study, a computational numerical modelling for corrosion simulation in reinforcing steel is developed. The corrosion simulation using Boundary element Method (BEM) and focusing for cylindrical reinforced concrete (RC). The main problem is high performance computer was required for the reinforced concrete corrosion simulation. Therefore, main purpose of this study is to reduce the needs of high-performance computer during the corrosion simulation. For the purpose, axisymmetric computational problem was integrated to the numerical BEM that considered able to reduce the computational effort. On the analysis process, the whole axial RC structures column was modeled by Laplace equation. The boundary condition for the corroded and non-corroded areas on the reinforcing steel (rebar) were represented by their established polarization curve. The Laplace equation was solved by BEM, thereby the potential on the structure can be analyzed. The simulation results show the similar potential distribution between BEM computational modelling by triangle element mesh and improvement BEM using axisymmetric element mesh problem. The simulation shows a significant differences, thereby the corrosion simulation using axisymmetric element mesh problem significantly reduces the computer effort in term of time-consuming and computer effort for the simulation. Thus, the improvement of the axisymmetric modelling for BEM becomes a powerful method for reducing the computational effort in term of cylindrical reinforcing steel corrosion simulation. Keywords— corrosion modelling, axisymmetric, BEM, cylindrical column, reinforced concrete